Assessing Financial Security of Low-Income Households in the United States. Issue 3 (2nd July 2016) - Lee, Jae Min; Kim, Kyoung Tae
ABSTRACT: The authors used three financial ratios to measure the financial security of low-income households: the liquidity, debt-to-income (DTI), and solvency ratios. The analytic sample included nonretired households with incomes no greater than three times the poverty threshold as reported by the U.S. Census Bureau. From the 2010 Survey of Consumer Finances data set, the authors found that households in the higher poverty threshold were more likely to meet the recommended guidelines for the DTI and solvency ratios. This study provides important insights for researchers and policymakers in the areas of poverty and household finance.